Maxwell's guide to authority work - Maxwell, Robert L., 1957- (Chicago : American Library Association, 2002)
"Authority work is the linchpin of the library catalog. As Maxwell puts it, "Without authority control the burden is placed on the user to think of all the possible forms a cataloger might have used to give access in the catalog to a given author or subject." From one of the preeminent experts in the field, this step-by-step guide for ensuring that your library and staff are creating and maintaining authority records with the end user in mind is a must-have." "In this text, authority work is broken down to its most basic components so that you can trace and follow the preparation of a complete authority record. Helpful illustrations identify the key characteristics of good authority records, common acronyms are defined, and cross-references throughout reinforce material." "The authoritative tool for making certain a person, author, corporate body, organization, book, or other media is appropriately accessible under its authority name, subject, and form, Maxwell's should be part of any library's toolbox."--Jacket.
Standards governing authority control -- Basic authority control procedures -- Authority control of names -- Uniform titles: general information -- Uniform titles: particular problems -- Series: general information -- Series authority records -- Authority control of terms: thesaurus building -- Authority control of terms: subjects -- Authority control of terms: genre/form -- The library and beyond.
Includes bibliographical references and index.
NLJCols20082021
Keywords: Authority files (Information retrieval); Fichiers d'autorit e; Authority files (Information retrieval); Standaardisatie; Catalogisering; Information Management; Vocabulary, Controlled; Subject Headings